Structural and optical properties of In2S3 thin films deposited by sulfurization assisted thermal evaporation method. (2021) - Chaudhary, Minakshi; Doiphode, Vidya; Shinde, Pratibha; Punde, Ashvini; Vairale, Priti; Hase, Yogesh; Waghmare, Ashish; Prasad, Mohit; Jadkar, Sandesh
Abstract: Indium sulfide (In2 S3 ) films were deposited onto soda lime glass by sulfurization assisted thermal evaporation method at different sulfurization temperatures. These films are further annealed for 1 hr at 300 °C. The structural, morphology and optical properties of these films are studied using x-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), energy dispersive x-ray analysis (EDAX), Raman and UV–Visible spectroscopy. Low angle-XRD analysis revealed that all films are polycrystalline in nature and confirmed the formation of only cubic phase of In2 S3 . The FE-SEM and EDAX analysis revealed significant change in the film morphology and composition upon sulfurization and annealing temperature. UV–Visible spectroscopy analysis showed that all films have strong absorption in visible region of the spectrum. With increase in sulfurization and annealing temperature the band gap increases and is found in the range 1.57–2.12 eV. However, band gap of In2 S3 thin films deposited at different sulfurization temperature are higher than those obtained after annealing of films.